2015
DOI: 10.5830/cvja-2015-033
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of full-fat milk and diluted lemon juice in reducing infra-cardiac activity of 99mTc sestamibi during myocardial perfusion imaging

Abstract: BackgroundWhen using 99mTc sestamibi for myocardial perfusion imaging, increased splanchnic activity creates a problem in the visual and quantitative interpretation of the inferior and infero-septal walls of the left ventricle. We sought to determine whether the administration of diluted lemon juice or full-fat milk would be effective in reducing interfering infra-cardiac activity and therefore result in an improvement in image quality. We compared the administration of full-fat milk and diluted lemon juice to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This might potentially be achieved by stimulating gall bladder contraction with a (fatty) meal around the time of tracer injection, which would result in faster passage of the tracer from the liver to duodenum. This method is commonly used in nuclear medicine for myocardial perfusion imaging [ 5 , 6 , 7 , 8 , 9 ]. Several high-fat meals have been investigated in the field of myocardial perfusion, such as milkshakes [ 6 ], full-fat milk [ 7 , 8 ], and chocolate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might potentially be achieved by stimulating gall bladder contraction with a (fatty) meal around the time of tracer injection, which would result in faster passage of the tracer from the liver to duodenum. This method is commonly used in nuclear medicine for myocardial perfusion imaging [ 5 , 6 , 7 , 8 , 9 ]. Several high-fat meals have been investigated in the field of myocardial perfusion, such as milkshakes [ 6 ], full-fat milk [ 7 , 8 ], and chocolate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method is commonly used in nuclear medicine for myocardial perfusion imaging [ 5 , 6 , 7 , 8 , 9 ]. Several high-fat meals have been investigated in the field of myocardial perfusion, such as milkshakes [ 6 ], full-fat milk [ 7 , 8 ], and chocolate [ 9 ]. Our hospital uses chocolate as a fatty meal between injection and myocardial perfusion imaging, and therefore chocolate was selected for this study as well.…”
Section: Introductionmentioning
confidence: 99%
“…Still, their respective pharmacokinetic and pharmacological interactions with other medications remain poorly studied. To prevent artefacts, different volumes of carbonated water, 3 soda, 4 lime, 5 lemon juice, 6 milk, 7 caffeine 8 or several of them combined 9 have already been empirically experimented as more or less efficient and accessible corrective actions. Their benefits were either attributed to acidity‐related increased hepatobiliary excretion or to gastric distension, lowering the radiotracer uptake.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The study by Boz et al indicates that eating solid and liquid foods before the resting stage reduced intestinal activity in Tc-99m tetrofosmin myocardial perfusion [19,20]. Also, Purbhoo et al showed that diluted lemon juice and milk reduced significantly infracardiac radiation in myocardial perfusion scan with radiopharmaceuticals Tc-99m sestamibi, which this reduction in the milk group had been more prominent [21]. The purpose of our studies was to determine what steps should be taken before resting the SPECT myocardium so that we can reduce the side effects of the liver, intestine, and stomach interactions.…”
Section: Introductionmentioning
confidence: 98%